ENGLISH FUN: TRANSFORMING ENGLISH LEARNING INTO SOFT SKILLS DEVELOPMENT - Muthmainnah Mursidin; Sitti Nurjannah; Jusmaniar Nonci; Rizka Indahyanti; Sulviana Sulviana; Muhammad Chairil Imran (Community Development Journal : Jurnal Pengabdian Masyarakat, 2026)
Students' English proficiency relates not only to linguistic ability but also to the development of soft skills essential in academic and professional environments. However, English instruction often focuses primarily on linguistic mastery, leaving opportunities to cultivate self-confidence, communication skills, collaboration, creativity, and problem-solving abilities underutilized. This community service initiative aims to enhance students' English proficiency while simultaneously developing their soft skills. The program employed a participatory and communicative approach, using English games, icebreakers, role-playing, storytelling, group discussions, presentations, and team-based challenges. The results demonstrated a positive response and increased student engagement in actively using English. Furthermore, the training provided students with opportunities to build self-confidence, communicate, collaborate, foster creativity, and engage in collaborative problem-solving, all of which support capacity building and prepare them to meet the demands of the academic and professional worlds.